1988
DOI: 10.1037/h0091778
|View full text |Cite
|
Sign up to set email alerts
|

ProsthesisWare: A new class of software supporting the activities of daily living.

Abstract: To use the microcomputer as a prosthetic tool in rehabilitation has a number of advantages over using it as a tutor for cognitive retraining. As a tool, the microcomputer program directly addresses ecologically relevant issues in activities of daily living. New classes of software like HyperCard™ and MacLaboratory Con-troller©, can be readily customized for each patient's needs. Unlike tutors used for cognitive retraining, rehabilitation tools provide prosthetic support that does not presuppose any required re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results of many of these interventions have been discouraging (see Cicerone et al, 2000, for a comprehensive review of interventions that do and do not appear to remediate cognitive dysfunction; see Majid, Lincoln, & Weyman, 2004, for a limited but critical review of cognitive rehabilitation interventions for stroke). Therefore, for individuals having persisting disabilities, interventions are typically considered that stress compensatory strategies for task completion (Chestnut et al, 1999; Chute, Conn, DiPasquale, & Hoag, 1988; Cole, Dehdashti, Petti, & Angert, 1994; Levine, Horstmann, & Kirsch, 1992; Rothi & Horner, 1983).…”
Section: What Are the Characteristics Of Atc Interventions?mentioning
confidence: 99%
“…The results of many of these interventions have been discouraging (see Cicerone et al, 2000, for a comprehensive review of interventions that do and do not appear to remediate cognitive dysfunction; see Majid, Lincoln, & Weyman, 2004, for a limited but critical review of cognitive rehabilitation interventions for stroke). Therefore, for individuals having persisting disabilities, interventions are typically considered that stress compensatory strategies for task completion (Chestnut et al, 1999; Chute, Conn, DiPasquale, & Hoag, 1988; Cole, Dehdashti, Petti, & Angert, 1994; Levine, Horstmann, & Kirsch, 1992; Rothi & Horner, 1983).…”
Section: What Are the Characteristics Of Atc Interventions?mentioning
confidence: 99%
“…Townes et al (1985) suggested that combining cognitive and affective measures provides a means of determining compensation for neurologic deficits that is more valuable than one which correlates diagnostic profiles with neurologic deficiencies. Chute, Conn, DiPasquale, & Hoag (1988) agreed, noting further that continuing improvements in neuroradiological techniques have decreased the need for localization of brain dysfunction as a primary objective for neuropsychological testing. With specific references to psychiatric cases, Erickson and Binder (1986) advocated testing with a primary goal of enhancing the patient’s functional skills.…”
mentioning
confidence: 99%